Modeling non-uniform thermal environment of stratum ventilation with supply and exit air conditions. (15th October 2018) - Zhang, Sheng; Cheng, Yong; Huan, Chao; Lin, Zhang
Abstract: The information (e.g., indoor air temperature and velocity distributions) of the non-uniform thermal environment is the base of the proper operation control of stratum ventilation for thermal comfort and energy efficiency. The current practice of modeling the non-uniform thermal environment requires inputs of the wall temperatures/heat fluxes, which increases the cost and complexity of the sensors because the building management system generally does not monitor the wall temperatures/heat fluxes. This study proposes to model the non-uniform thermal environment with the supply and exit air conditions as inputs. The supply and exit air conditions (i.e., the supply air temperature, supply airflow rate and exit air temperature) can be obtained readily from the building management system. Twenty-eight experiments of two stratum ventilated rooms with different geometries, heat source distributions and air terminal layouts have demonstrated that the proposed method can accurately predict the vertically and horizontally non-uniform distributions of the indoor air temperature and velocity, with root mean square errors (RMSEs) between 0.13 °C and 0.22 °C and between 0.008 m/s and 0.039 m/s respectively. For the dynamic control of stratum ventilation, the models of the indoor air temperatures from the experiments under steady states are found to apply to the dynamic variations of the indoor air temperatures from around 24 °C–30 °C, with RMSEs between 0.28 °C and 0.37 °C. The proposed method has also been experimentally validated to apply to displacement ventilation. Highlights: Method is proposed to model non-uniform thermal environment of stratum ventilation. Supply and exit air conditions are used as inputs. Vertical and horizontal non-uniformities of indoor air temperature and velocity are modeled. RMSEs of indoor air temperature and air velocity are less than 0.37 °C and 0.039 m/s respectively. Proposed method is also applicable to displacement ventilation.